Angiolymphoid hyperplasia with eosinophilia: a case report - Youssef, Alexey (J Med Case Rep, 2018)
BACKGROUND: Angiolymphoid hyperplasia with eosinophilia is a benign neoplasm that includes blood vessel proliferation and a dense eosinophilic inflammatory infiltrate. Mostly, it affects middle-aged adults manifesting as flesh/plum-colored pruritic nodules and papules, most commonly affecting the ear and the periauricular area. CASE PRESENTATION: In this case, we report a 13-year-old Caucasian girl with bilateral, huge, protruding, and yellowish nostril masses which were peculiar in location and of gross appearance. At first, the disease proved to be a diagnostic dilemma. After making a diagnosis of angiolymphoid hyperplasia with eosinophilia, the disease also proved to be a therapeutic dilemma. It did not respond to oral prednisolone or to oral indomethacin, and it proved to be resistant to topical steroids. Although surgery is the standard therapeutic approach, it recurred despite multiple surgical attempts. However, the only regimen that seemed to partially control the lesion was intralesional steroids combined with topical tacrolimus ointment. CONCLUSIONS: Angiolymphoid hyperplasia with eosinophilia proves a therapeutic dilemma, because there is a large variety of proposed treatments, yet there is not enough data on most of them. Although the disease is not deadly by itself, it usually presents with disfiguring lesions that grimly affect the patient’s quality of life. This warrants further research and efforts to find an effective cure and a unified therapeutic approach.